Equal Incremental Cost Method dengan Adjustable Gamma Control untuk Menyelesaikan Penjadwalan Pembangkit - Basuki Rahmat; I Gede Putu Oka Indra Wijaya; Rifki Rahman Nur Ikhsan; Lindiasari Martha Yustika; Jangkung Raharjo (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
Generator scheduling remains an intriguing issue within the energy industry. It relates to the optimization of production costs, where system operators must select the optimal combination of available resources to minimize production costs. This paper proposes an enhancement to the Equal Incremental Cost (EIC) Method using Adjustable Gamma Control (AGC) in generator scheduling. Iterations begin with an initial lambda value, then gradually increase with the application of the factor until power demand is met. A variable of 10% is used as an adjustment step in the optimization method. The proposed method is capable of achieving convergence with 100% accuracy, where the power generated by all generators precisely matches the load demand (2,650 MW), at a cost of USD 32,289.03. EIC-AGC ranks second-best after VLIM, albeit with the consequence of consuming 195 seconds. This method is expected to have a significant impact on designing highly accurate economic dispatch techniques. Thus, generator scheduling will lead to a reduction in operational costs compared to current practices.